Dynamic Systems Model of Organizational Performance in Improving Public Service Quality of BPS In Bandung Raya Region - Ahmaddien, Iskandar; Purwanto, Bambang Heru; Aziz, Yaya Mulyana Abdul (Journal of Ecohumanism, 2024)
Initial analysis shows that the performance of BPS in Bandung Raya has not provided maximum results. This has an impact on the non-optimal quality of BPS public services in Bandung Raya. By using descriptive analysis, SEM, and system dynamics, this research seeks to determine the implementation of BPS performance in Bandung Raya, analyze the factors that hinder the quality of public services, and analyze what performance models are effective in improving the quality of BPS public services in Bandung Raya. The results showed that there are still several things that need to be improved related to the strategy, process, and capability of BPS in Bandung Raya. From these three aspects, it was found that the process and organizational capability had a positive and significant effect on the quality of BPS services in Bandung Raya, while the business strategy did not have a significant effect. Several factors that hinder the performance and effectiveness of BPS services in Bandung Raya were also found. These factors are related to transformational leadership, training for human resources, technology and information, and data integrity. Therefore, this research provides 5 scenarios obtained based on the results of system dynamics simulation to be used as policy proposals. Of the 5 scenarios, it is found that scenario V, namely data integrity, is the best scenario because it is able to improve organizational performance up to 76.01% and service quality up to 70.82%. By applying the novelty of this research, it is expected to improve the quality of BPS public services in Bandung Raya.